Influence of seasonality on the haematological and biochemical parameters of native species Rhamdia quelen - Fredianelli, Ana Carolina; do Amaral Gurgel Galeb, Luciana; Venâncio Mangrich da Rocha, Rita Maria; Pizzolato Montanha, Francisco; Ribeiro, Deivid Roni; Anater, Amanda; Turra Pimpão, Cláudia (Revista Acadêmica Ciência Animal, 2018)
The objective of this study was to evaluate if there is any influence of the seasons on the homeostasis of silver catfish (Rhamdia quelen) through haematological and serum biochemistry evaluations. During one year, blood samples were collected from groups of 40 silver catfish in each season (spring, summer, autumn, and winter), totaling 160 animals. Blood samples were collected individually and used for haematological and serum biochemistry evaluations. In general, the main haematological findings were observed in the summer and in the spring, with hemoglobin levels (6.32 g.dL-1 ± 0.20), total erythrocyte counts (1.62 x 106.μL-1 ± 0.05) and neutrophil counts (14.21 x 10³.µL-1 ± 0.60) higher in the summer than in the other seasons (p < 0.05), whereas in the spring the total leukocyte count (25.89 x 10³.µL-1 ± 1.02) and the number of eosinophils (9.08 x 10³.µL-1 ± 0.11) were higher when compared to the other seasons (p < 0.05). The levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), alkaline phosphatase (ALP), gamma glutamyltransferase (GGT), and albumin levels were significantly altered between all seasons, but remained within the normal intervals for the species. Seasonality significantly influences haematological parameters and biochemical parameters of Rhamdia quelen, but without a clear determination of the types of change in each season.